2001
DOI: 10.1002/jclp.1060
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of fibromyalgia incorporating EEG‐Driven stimulation: A clinical outcomes study

Abstract: Thirty patients from a private clinical practice who met the 1990 American College of Rheumatology criteria for fibromyalgia syndrome (FS) were followed prospectively through a brainwave-based intervention known as electroencephalograph (EEG)-driven stimulation or EDS. Patients were initially treated with EDS until they reported noticeable improvements in mental clarity, mood, and sleep. Self-reported pain, then, having changed from vaguely diffuse to more specifically localized, was treated with very modest a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 39 publications
(32 reference statements)
4
67
0
Order By: Relevance
“…Many authors do not differentiate between types of phantom limb pain when applying biofeedback but still achieve success [122][123]. Regarding fibromyalgia, a series of studies have confirmed that a psychophysiological intervention combining sEMG biofeedback and EEG-driven stimulation effectively treats fibromyalgia [124][125][126]. These investigators identified diffuse muscular coactivation as a potential source of pain in fibromyalgia and successfully used sEMG biofeedback to reduce the pain in these tender points [124][125].…”
Section: Biofeedbackmentioning
confidence: 99%
“…Many authors do not differentiate between types of phantom limb pain when applying biofeedback but still achieve success [122][123]. Regarding fibromyalgia, a series of studies have confirmed that a psychophysiological intervention combining sEMG biofeedback and EEG-driven stimulation effectively treats fibromyalgia [124][125][126]. These investigators identified diffuse muscular coactivation as a potential source of pain in fibromyalgia and successfully used sEMG biofeedback to reduce the pain in these tender points [124][125].…”
Section: Biofeedbackmentioning
confidence: 99%
“…Biofeedback treatment, particularly electromyography biofeedback using surface electromyography (sEMG) procedures, show mixed results (Rossy et al, 1999;Schwartz, 1995;Simms, 1994). Donaldson, Nelson and Schulz (1998), Mueller, Donaldson, Nelson and Lyman (2001), and Flor, Birbaumer, and Turk (1990) suggested that the characteristic FMS neurosomatic symptoms (e.g., cognitive, mood, sleep) may be due to a neurosensitization process that becomes self-perpetuating through CNS-activated autonomic and musculoskeletal reactions, resulting in muscle ischemia and hypoxia and the release of pain-producing sub-stances in the periphery that feedback to the CNS. Thus, tender point abnormalities may represent secondary hyperalgesia, which depends on central nervous system pain mechanisms (Staud, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, tender point abnormalities may represent secondary hyperalgesia, which depends on central nervous system pain mechanisms (Staud, 2002). The outcome of this process may be a chronic generalized pain syndrome that is associated with EEG abnormalities and that may respond (i.e., by "CNS desensitization") to a brainwave-based biofeedback known as EEG biofeedback or neurofeedback (Budzynski, 1999;Mueller et al, 2001). Mueller et al (2001) treated a preliminary series of thirty patients primarily (n = 26) or exclusively (n = 4) with EEG-driven stimulation (EDS), a specific form of neurofeedback, and reported that a variety of FMS symptoms improved substantially.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This stimulation is believed to gently nudge the brain off of its stuck points, assisting it to become more flexible and self-regulating. Research (e.g., Donaldson, Sella, & Mueller, 1998;Mueller, Donaldson, Nelson, & Layman, 2001;Larsen, 2006;Schoenberger, Shiflett, Esty, Ochs, & Matheis, 2001), as well as clinical experience has found LENS rivals traditional forms of neurofeedback in the treatment of conditions such as traumatic brain injury, fibromyalgia, ADD/ADHD, depression, and other conditions (Larsen, 2006;Ochs, 1994Ochs, , 1996.…”
Section: Introductionmentioning
confidence: 99%